Encyclopedia of Life Sciences 2011
DOI: 10.1002/9780470015902.a0023170
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli Cotranslational Targeting and Translocation

Abstract: Targeting of proteins to their proper location inside the cell, in the membrane or in the extracellular space is crucial to the cell. The targeting information is provided in form of a signal sequence by the protein itself. In Escherichia coli , mostly membrane proteins are targeted cotranslationally via the signal recognition particle (SRP) to the membrane. The SRP and its receptor are both guanosine triphosphatases (GTPas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…coli membrane proteins are mostly dependent on the presence of the conserved Sec translocation machinery for their proper integration into the membrane bilayer [31].…”
Section: / Considerations For Cell-free Protein Synthesis Experimentmentioning
confidence: 99%
See 1 more Smart Citation
“…coli membrane proteins are mostly dependent on the presence of the conserved Sec translocation machinery for their proper integration into the membrane bilayer [31].…”
Section: / Considerations For Cell-free Protein Synthesis Experimentmentioning
confidence: 99%
“…Structure determination of the RNC-TF complex suggested that the co-translational folding of the nascent chain was favored by a protected environment formed by TF and the ribosome (Figure 3). Using a similar approach, several ribosomal complexes have been solved by cryo-EM providing important insights into the molecular mechanism of co-translational targeting and translocation [31]. For these studies a DNA sequence encoding the N-terminal part including the signal-anchor sequence of the E. coli membrane protein FtsQ was used to produce RNCs.…”
Section: 1/ Ribosome-nascent Chain Complexesmentioning
confidence: 99%
“…Sec-translocation is the dominant translocation pathway in E. coli [16]. This mechanism is believed to either co-or post-translationally translocate SecB-bound or SRP-directed polypeptides targeted for translocation by an N-terminal signal sequence [17][18][19][20]. This production mode is expected to avoid possible cytoplasmic SmEn toxicity and periplasmic protein folding can be facilitated after signal peptide removal by signal peptidase by the disulfide bond forming and isomerizing oxidoreductases DsbA and DsbC) [21,22].…”
Section: Introductionmentioning
confidence: 99%